Grips and Gestures on a Multi-Touch Pen - Song, Hyunyoung; Benko, Hrvoje; Guimbretiere, Francois; Izadi, Shahram; Cao, Xiang; Hinckley, Ken (CHI '11 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2011)
This paper explores the interactive possibilities enabled when the barrel of a digital pen is augmented with a multi-touch sensor. We present a novel multi-touch pen (MTPen) prototype and discuss its alternate uses beyond those of a standard stylus, such as allowing new touch gestures to be performed using the index finger or thumb and detecting how users grip the device as a mechanism for mode switch-ing. We also discuss the hardware and software implemen-tation challenges in realizing our prototype, and showcase how one can combine different grips (tripod, relaxed tripod, sketch, wrap) and gestures (swipe and double tap) to enable new interaction techniques with the MTPen in a prototype drawing application. One specific aim is the elimination of some of the comfort problems associated with existing aux-iliary controls on digital pens, such as barrel buttons and barrel scroll wheels; such mechanical controls work best in only a few specific hand grips and pen rotations. Compara-tively, our gestures can be successfully and comfortably performed regardless of the rotation of the pen or how the user grips it, offering greater flexibility in use. We describe a formal evaluation comparing MTPen gestures against the use of a barrel button for mode switching. This study shows that both swipe and double tap gestures are significantly faster than commonly employed barrel buttons after acqui-sition time is taken into consideration.